Nata De Coco Production with Addition of Antocyanin from Mangosteen Peel Extract - Pratama, Irawan Adi; Amalia, Rizka; Mario, Abraham (Journal of Vocational Studies on Applied Research, 2023)
Mangosteen peel is rich antioxidant compounds which are very beneficial for human health and this potential is being utilized by the community. Mangosteen peel extract contains anthocyanin compounds. Anthocyanin are considered as active compounds whose consumption is associated with beneficial health effects. Nata de coco has many benefits for health, especially digestion, because of its high fiber content, low calories, and does not contain cholesterol. This research examines the optimum operating conditions of the nata de coco production process with the addition of mangosteen peel anthocyanin extract and the characteristics of the resulting nata de coco. This research study was carried out with various variables including: The ratio between mangosteen peel extract and coconut water (1:19 and 9:1 (v/v)), fermentation time 10 and 13 days), and Acetobacter xylinum volume (2,5% and 10%). During the research, the water content of the mangosteen peel was analyzed for yield and Total Anthocyanin Content. The result product were tested in thickness, weight, organoleptic, pH, crude fiber content, and Total Anthocyanin Content of Nata de Coco.